2017
DOI: 10.3390/fractalfract1010014
|View full text |Cite
|
Sign up to set email alerts
|

A Solution to the Time-Scale Fractional Puzzle in the Implied Volatility

Abstract: Abstract:In the option pricing literature, it is well known that (i) the decrease in the smile amplitude is much slower than the standard stochastic volatility models and (ii) the term structure of the at-the-money volatility skew is approximated by a power-law function with the exponent close to zero. These stylized facts cannot be captured by standard models, and while (i) has been explained by using a fractional volatility model with Hurst index H > 1/2, (ii) is proven to be satisfied by a rough volatility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…It features a more complete structure than the simple composition of the time and space fractional models as it exhibits non trivial phenomena including larges jumps and memory effects, which can not be understood as a simple market time re-parametrization of an α-stable process. Let us also mention that it has also found many applications in real systemsfinancial processes representing one of the most promising fields, where the fractional diffusion and generally fractional calculus has been successfully applied [2,12,20,22,21,35,41,42].…”
Section: Introductionmentioning
confidence: 99%
“…It features a more complete structure than the simple composition of the time and space fractional models as it exhibits non trivial phenomena including larges jumps and memory effects, which can not be understood as a simple market time re-parametrization of an α-stable process. Let us also mention that it has also found many applications in real systemsfinancial processes representing one of the most promising fields, where the fractional diffusion and generally fractional calculus has been successfully applied [2,12,20,22,21,35,41,42].…”
Section: Introductionmentioning
confidence: 99%
“…The first generalization of Black-Scholes model [5,6] to the model with stable distributions was the Finite moment log-stable option pricing model introduced by Carr and Wu [7]. Later several other models were introduced that included timefractional [13,21,10] derivatives, space-fractional derivatives, [8] space-time fractional derivatives [20,1,2,3,4] derivatives of fractional order [22], etc. It has been shown that the orders of fractional derivatives play the role of risk redistribution parameters in price and time [20].…”
Section: Applications To Option Pricing Modelmentioning
confidence: 99%
“…Another empirical work concerning option implied measurement of the Hurst exponent was conducted by Flint and Mare (2016). Funahashi and Kijima (2017) further contributes to this fractal literature by modeling the relationships between the short and long ends of the term structure of volatility to estimate the implied Hurst exponent.…”
Section: Related Literaturementioning
confidence: 99%